PRACTICALITY OF STUDENTS WORKSHEET OF PLANE FIGURE USING CARTOONS DESIGN - Yolanda, Nela Sari (Universitas Negeri Surabaya, 2019)
The purpose of this research is to determine the practicality of Student Worksheets of Plane Figure topics with cartoons design. Practicality is indicated by how be convinience to using the worksheet, a time required in the implementation and students' attractiveness of Student Worksheets on students' learning interests. Students' Worksheets are wished have to influence student learning outcomes and are expected to increase the learning interest of Grade 3 students at SDN 20 Muaro Sijunjung in plane figure topics. The research procedure used the Instructional Development Institute (IDI) model that applied principles of the system approach, discovery (define) or needs analysis, development (develop) and evaluation (evaluate). Practicality is investigated through observation of implementation of teaching and learning process, giving questionnaires of learning interest to students, and interviews students and teachers. Analysis data was carried out descriptively. The results of the learning interest questionnaire can be concluded practically with an average of 78.96%. The results of interviews with students and teachers that LKS with cartoon images are practical from the ease of use, time used, and attractive to students.